Fentanyl versus tramadol as a supraclavicular brachial plexus blockade (BPB) - Saad Kamel, Hayder; Asi Jabbar, Mohammad; Salem Yahya, Mohammad (International Journal of Psychosocial Rehabilitation, 2021)
In anesthetists, there is limited information regarding the use of opioids as adjuvants in brachial plexus blockade (BPB). We conducted a study comparing fentanyl and tramadol as local anesthetic adjuvants in supraclavicular BPB. The study included 50 patients, divided into two groups: Group F, which received 2 ml of fentanyl, and Group T, which received 2 ml of tramadol. Data were collected on the onset and duration of nerve block. The onset of sensory and motor blockade was significantly faster (p = 0.01) in Group T compared to Group F. Additionally, the time to the first analgesic request was significantly longer in Group T compared to Group F (p = 0.01). Tramadol in ultrasound-guided supraclavicular BPB produced a significantly longer duration of analgesia and a shorter onset of nerve blockade.